2018
DOI: 10.3390/nu10020204
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lycopene Concentrations and Associations with Clinical Outcomes in a Cohort of Maternal-Infant Dyads

Abstract: Oxidative stress has been associated with adverse neonatal outcomes, and many carotenoids, including lycopene, potentially have antioxidant properties. The objective of this analysis was to explore the associations between serum lycopene concentrations, including lycopene isomers, and maternal-newborn outcomes. Maternal and cord blood samples were collected in 180 mother-infant pairs. Serum of total lycopene as well as the cis- and trans-isomers concentrations were measured using HPLC (High Performance Liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Interestingly, an increased carotenoid concentration was associated with a significantly reduced risk of both mild and severe SGA in this same study [ 38 ]. Other studies have shown positive associations between maternal carotenoid status and infant growth, specifically lycopene [ 39 ]. As far as we know, our study is the first to report that maternal levels of α- and β-carotenoids are higher in mothers of growth-restricted infants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an increased carotenoid concentration was associated with a significantly reduced risk of both mild and severe SGA in this same study [ 38 ]. Other studies have shown positive associations between maternal carotenoid status and infant growth, specifically lycopene [ 39 ]. As far as we know, our study is the first to report that maternal levels of α- and β-carotenoids are higher in mothers of growth-restricted infants.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of studies highlight the importance of lutein during the neonatal and infancy period due to its role during neuro and visual development, as well as reducing oxidative stress and the risk of disorders associated with prematurity [6,7,24,26]. However, lycopene may also decrease the risk of adverse neonatal outcomes (birth parameters, Respiratory Distress Syndrome, Newborn Intensive Care Unit admission), as shown in a recently published study which assessed the maternal serum lycopene during pregnancy in 180 maternal-infant pairs from the USA [53].…”
Section: Discussionmentioning
confidence: 99%
“…The current study highlights the antiulcerative effect of SP aqueous extract against EtOH-induced gastric ulceration in rats. This antiulcerative potential might be due to the antioxidant ingredients found in SP aqueous extract such as lycopene [ 31 ], α -linolenic acid [ 32 ], oleic acid [ 33 ], lycoxanthin [ 34 ], and retinoic acid [ 35 ].…”
Section: Discussionmentioning
confidence: 99%